2019
DOI: 10.1093/mnras/stz1479
|View full text |Cite
|
Sign up to set email alerts
|

The nature of strong H i absorbers probed by cosmological simulations: satellite accretion and outflows

Abstract: We use state-of-the-art cosmological zoom simulations to explore the distribution of neutral gas in and around galaxies that gives rise to high column density H i Ly-α absorption (formally, sub-DLAs and DLAs) in the spectra of background quasars. Previous cosmological hydrodynamic simulations under-predict the mean projected separations (b) of these absorbers relative to the host, and invoke selection effects to bridge the gap with observations. On the other hand, single lines of sight (LOS) in absorption cann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 101 publications
5
20
0
Order By: Relevance
“…Combining with the results of subDLAs being on average more metal poor than DLAs, this could potentially imply that subDLAs tend to trace CGM-like rather than ISM-like environments more frequently than DLAs (Fumagalli et al 2011). Rhodin et al (2019) analysed zoom-in simulations of a Milky Way-like progenitor and found subDLAs and DLAs arising in the galaxy CGM, but with higher metallicities than measured from the XQ-100 subDLAs. Future cosmological simulations with improved resolution in CGM environments (e.g.…”
Section: Ionization Effectsmentioning
confidence: 80%
See 1 more Smart Citation
“…Combining with the results of subDLAs being on average more metal poor than DLAs, this could potentially imply that subDLAs tend to trace CGM-like rather than ISM-like environments more frequently than DLAs (Fumagalli et al 2011). Rhodin et al (2019) analysed zoom-in simulations of a Milky Way-like progenitor and found subDLAs and DLAs arising in the galaxy CGM, but with higher metallicities than measured from the XQ-100 subDLAs. Future cosmological simulations with improved resolution in CGM environments (e.g.…”
Section: Ionization Effectsmentioning
confidence: 80%
“…While the Mg II pre-selection provides an efficient use of space-based resources (Rao et al 2017), it potentially leads to the selection of metal-rich systems (Ellison 2006;Murphy et al 2007; Dessauges-Zavadsky, Ellison & Murphy 2009;Berg et al 2017). Using simulations, Rhodin et al (2019) demonstrated that the mass difference of DLAs and subDLA host is an effect of the gas cross-section selections, primarily at z < 1. Despite several large literature compilations of blind (Rafelski et al 2012) or uniformly selected DLA studies (Jorgenson et al 2013), there are only a few blind literature compilations or homogeneous samples of subDLA metal abundances available (Dessauges-Zavadsky et al 2003;Prochaska et al 2015;Quiret et al 2016, with respective sample sizes of 12, 99, and 92 subDLAs).…”
mentioning
confidence: 99%
“…Many groups, including FOGGIE, have recently shown that better spatial resolution in the simulated CGM leads to a natural development of small clouds (van de Voort et al 2019;Peeples et al 2019;Rhodin et al 2019;Suresh et al 2019), largely because once the cooling length of the gas is resolved the gas can cool and condense into smaller structures (Hummels et al 2019;Zheng et al 2020). Importantly for comparisons to observables such as metallicity, improved spatial resolution in the low-density gas also reduces the artificial mixing of metals, thereby allowing gas to remain at "high" and "low" metallicities even in the CGM; that is, while the median metallicities do not change much, the scatter about that median increases with improved resolution (Corlies et al 2020).…”
Section: Motivation and Methodologymentioning
confidence: 99%
“…The individual small-scale structures that contribute to the observed absorption profiles can therefore be resolved. These small-scale structures that become only apparent in highresolution simulations are hosts to a significant amount of cool gas, enhancing the column densities in especially the low ionization state of the gas (Peeples et al 2019;Corlies et al 2020; see also Hummels et al 2019;Rhodin et al 2019;van de Voort et al 2019).…”
Section: Quantitative Comparison In the Cgm Variation Betweenmentioning
confidence: 99%